Assessment of Contaminants of Emerging Concern and Antibiotic Resistance Genes in the Mapocho River (Chile): A Comprehensive Study on Water Quality and Municipal Wastewater Impact - Garcia-Mena, V (Elsevier B.V., 2024)
The primary objective of this study was to evaluate the persistence and elimination of Contaminants of Emerging Concern (CECs) in municipal wastewater treatment plants (MWWTPs) and their presence in the Mapocho River within the metropolitan area of Santiago, Chile. The use of advanced analytical techniques, based on liquid chromatography coupled to both low and high-resolution mass spectrometry, allowed a comprehensive overview on the presence of CECs in samples. Additionally, a preliminary assessment of the microbiological aspects aimed to determine the presence of indicator microorganisms of fecal contamination, such as Escherichia coli and total coliforms was conducted. Furthermore, a qualitative assessment of Antibiotic Resistant Genes (ARGs) was performed. No CECs were detected upstream to the MWWTPs. However, the results from various wastewater samples (influent, secondary, and tertiary effluents) revealed significant diversity, with 73 CECs detected alongside prevalent ARGs including sulI, sulfII, qnrB, and blaTEM. The presence of CECs and ARGs downstream of the MWWTP in the Mapocho River was mainly attributed to effluent discharge. On the other hand, typical values for a healthy river and a MWWTP with a final disinfection stage were found in terms of fecal contamination. Consequently, the imperative for developing tertiary or quaternary treatments capable of degrading CECs and ARGs to minimize environmental impact is underscored. These findings hold public health significance, offering insights into potential risks and influencing future legislative measures in Chile. © 2024 Elsevier B.V.